2012
DOI: 10.1590/s0100-06832012000100015
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade dos índices de colheita de nutrientes em genótipos de feijoeiro e sua relação com a produção de grãos

Abstract: A identificação de genótipos com elevada acumulação de biomassa e nutrientes, mas com baixo índice de colheita de nutrientes (razão entre conteúdo de nutrientes nos grãos e na parte aérea), pode reduzir a remoção pelas colheitas e aumentar a sustentabilidade agrícola. Evidências de reduzida variabilidade nos índices de colheita em feijoeiro (Phaseolus vulgaris L.) demandam a avaliação de uma ampla gama de genótipos. Este trabalho teve como objetivo avaliar a variabilidade dos índices de colheita de nutrientes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
1
3
1
2
Order By: Relevance
“…The HI shows the extent of photoassimilates sent to grain and, consequently, plant translocation efficiency. In an experiment evaluating HI and the relationship with grain yield in the State of Rio de Janeiro, the average HI of cultivars was 61.9%, higher than that found in the present study (Araújo & Teixeira, 2012). The reason for the low HI observed in our study was probably due to the high incidence of anthracnose.…”
Section: Resultscontrasting
confidence: 88%
“…The HI shows the extent of photoassimilates sent to grain and, consequently, plant translocation efficiency. In an experiment evaluating HI and the relationship with grain yield in the State of Rio de Janeiro, the average HI of cultivars was 61.9%, higher than that found in the present study (Araújo & Teixeira, 2012). The reason for the low HI observed in our study was probably due to the high incidence of anthracnose.…”
Section: Resultscontrasting
confidence: 88%
“…O conteúdo de N nos grãos variou entre 5,70 e 8,18 g m -2 , com valores maiores nas cultivares BRS Pontal, BRS Vereda, BRS Campeiro e Aporé. Westermann et al (2011) observaram média de 6,4 e 15,0 g m -2 para conteúdo de N nos grãos de 16 genótipos de feijoeiro-comum, em sistema orgânico de baixo e alto ingresso de insumos, respectivamente, enquanto Araújo & Teixeira (2012) observaram média de 10,3 g m -2 para 64 genótipos de feijoeiro em cultivo convencional, superior à média de 6,5 g m -2 observada no presente estudo. As cultivares de feijoeiro-comum avaliadas diferiram quanto à produção de grãos e aos componentes de produção nos dois experimentos, o que indica variabilidade no desempenho de cultivares, em sistema orgânico de produção, que também é afetada pelas condições ambientais de cultivo (Singh et al, 2009).…”
Section: Resultsunclassified
“…However, others symptoms such as plant growth and reduction of shoot biomass are not considered on this scale, besides happening in screening essays. Andrade et al (2009) and Araújo and Teixeira (2012) reported that genotypes with reduced biomass production have lower grain yield. Facing these divergent results related to the performance of resistant-parents, stunted growth must also be taken into account in the selection of parents for Fusarium wilt resistance.…”
Section: General Combining Abilitymentioning
confidence: 99%